The Impact of the Auditor's Change on the Reaction of the Capital Market: Empirical Study on the Amman Stock Exchange - Alhaija, Mohammed Fawzi (International Journal of Economics and Financial Issues, 2017)
The purpose of this paper is to examine the influence of information disclosure such as changing the auditor on evaluating the inspected company in the capital market. This article covers cases where the auditor changes during the period without going through the general resolution of the general meeting of shareholders, and the temporary accounting auditor is appointed accordingly (replacement during the term). The replacement during the term is one of the major features of the change in the auditor in Jordan that is not in the US for example, which might be a bad news for investors. In this paper, we compared the Cumulative Anomaly Return (CAR) with the replacement in the middle of the year and the usual replacement, and examined the effect of the replacement during the term on the stock price of the company being inspected. As a result, an evidence was obtained suggesting that the capital markets responded more negatively to replacement during the period than normal replacement. In other words, the information of the replacement during the term implies a negative information value for investors, which means that it can be a factor that causes a negative investing behavior. Keywords: change of auditor, capital markets, cumulative abnormal return (CAR). JEL Classifications: F3, M4